Uniportal versus multiportal video-assisted thoracoscopic surgery does not compromise the outcome of segmentectomy. (24th November 2020) - Xie, Dong; Wu, Junqi; Hu, Xuefei; Gonzalez-Rivas, Diego; She, Yunlang; Chen, Qiankun; Zhu, Yuming; Jiang, Gening; Chen, Chang
Abstract: OBJECTIVES: The goal of this study was to compare the feasibility and safety of uniportal thoracoscopic segmentectomy (UTS) with that of multiportal thoracoscopic segmentectomy (MTS). METHODS: From January 2014 to December 2015, a total of 1056 patients who underwent thoracoscopic segmentectomy were identified, including 375 and 681 who had simple and complex segmentectomies, respectively. A propensity matched analysis was applied to compare perioperative indicators. Survival outcomes, which included disease-free survival and overall survival, were assessed by Kaplan–Meier estimates and Cox hazards regression analysis. RESULTS: Propensity matching generated 454 paired patients for the UTS and MTS cohorts; the perioperative results were comparable. Survival analysis indicated that the surgical approach (UTS versus MTS) was not an independent risk factor in either disease-free survival ( P  =   0.247) or overall survival ( P  =   0.870) of patients with invasive adenocarcinoma. A shorter operative time was observed in patients who had a UTS ( P  <   0.001) or an MTS ( P  =   0.011) via a simple segmentectomy compared with those who had a complex segmentectomy. Moreover, 147 and 266 corresponding cases were selected to compare the UTS and MTS in the simple and complex segmentectomy groups, respectively. MTS showed slightly longer operative times (119 vs 108 min; P  =   0.007) and drainage duration ( P  =   0.010) in the simple segmentectomy group. In contrast, UTS was associated with statistically longer operative times (141 vs 133 min; P  =   0.016) in the complex segmentectomy group. CONCLUSIONS: Although minor differences could be found in the simple and complex segmentectomy groups, respectively, these results were clinically irrelevant. Our study supports UTS as a feasible and safe surgical technique.